STUDIES OVER CHARACTERISTICS SHAPING RESIDENTIAL ATTRACTIVENESS OF SUBURBAN RURAL AREAS - Źróbek-Różańska, Alina; Zysk, Elżbieta; Źróbek-Sokolnik, Anna (Acta Scientiarum Polonorum. Oeconomia, 2016)
Nearly every third migrating person in Poland is found to have moved out of the city and into a rural area near big cities. Local authorities should analyze governed area in the terms of residential attractiveness and identify the most attractive localizations prone to residential development concentration. The aim of the article was to apply the weighted additive rule to identify the most attractive areas. It required creating the potential newcomer's profile and the list of demanded characteristics equipped with weights. It appeared that potential newcomers would be people in their 25-40 with small children, with the ability to achieve mortgage credit, higher education and strong links with neighboring city. The strongest impact on their decision would have low price of real estate, lack of burdensome objects, full access to media and neat surroundings. The scarcity of some characteristics can be compensated by the high quality of the others, and the level of compensation depends on the prescribed weights.